2021
DOI: 10.1037/sgd0000501
|View full text |Cite
|
Sign up to set email alerts
|

“Previous resilience has taught me that I can survive anything:” LGBTQ resilience during the COVID-19 pandemic.

Abstract: Coronavirus disease 2019 (COVID-19) has disproportionately negatively affected the lesbian, gay, bisexual, transgender, and queer (LGBTQ) community, a group who faces identity-based marginalization in society. LGBTQ resilience narratives are important in buffering against the negative impact of minority stress, but little is known about how LGBTQ people have been resilient during the COVID-19 pandemic. The current research addresses this gap in the literature. Participants included 129 LGBTQ individuals who sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 71 publications
3
46
0
3
Order By: Relevance
“…In LGBTQI2S+ (lesbian, gay, bisexual, transgender, queer/questioning, intersex, two spirited and other not named sexual and gender identities) populations, participants referred to resilience because of lessons learned from previous experiences with hardship, e.g., in the United States ( Abreu et al, 2021 ; Gonzalez et al, 2021 ; Quinn et al, 2021 ), and radical acceptance of, e.g., their identity, and the everyday commitment to one’s identity and acknowledgment of having a privileged position with access to resources and care ( Gonzalez et al, 2021 ). Resilience referred to embracing collective and individual aspects at such a meta-level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In LGBTQI2S+ (lesbian, gay, bisexual, transgender, queer/questioning, intersex, two spirited and other not named sexual and gender identities) populations, participants referred to resilience because of lessons learned from previous experiences with hardship, e.g., in the United States ( Abreu et al, 2021 ; Gonzalez et al, 2021 ; Quinn et al, 2021 ), and radical acceptance of, e.g., their identity, and the everyday commitment to one’s identity and acknowledgment of having a privileged position with access to resources and care ( Gonzalez et al, 2021 ). Resilience referred to embracing collective and individual aspects at such a meta-level.…”
Section: Resultsmentioning
confidence: 99%
“…They also contributed to building and providing social resources by caring for the community. In turn, this also meant that, in an example from the United States, they benefited from giving, which increased their own feeling of resilience ( Gonzalez et al, 2021 ) and collective and self-efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…By attending to these experiences, especially given the context of this community’s history with global health crises, practitioners will be better suited to effectively help their LGBTQ clients process how the effects of the COVID-19 pandemic can be buffered by actively seeking and providing community support. For example, given recent research to support that LGBTQ people have been able to access community though online platforms (e.g., Gonzalez et al, in press), one way to provide an affirming space for LGBTQ clients is for clinicians to facilitate online groups for LGBTQ people to come together. This would allow for community to be more accessible to LGBTQ individuals, especially those who might not have access to LGBTQ community centers such as in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the study inquired about: (a) experiences and impact of isolation, (b) resilience, and (c) community and cultural values as a source of strength. The authors wrote one other article from this dataset that focused on how resilience has informed LGBTQ peoples’ reactions to the COVID-19 pandemic (Gonzalez et al, in press). Given the richness of the data collected and the participants’ extensive narratives about how community and cultural values have served as sources of strength for LGBTQ people during the COVID-19 pandemic, it was important to have one article focused on this area.…”
Section: Methodsmentioning
confidence: 99%
“…Structural stigma, including discriminatory social policies, can greatly harm LGBTQ + well-being (Hatzenbuehler, 2014 ), and our findings can be used to inform policies and community programming that promotes equity across all social identities through the depoliticization of public health. Policies and programs must also center and foster LGBTQ + people’s capacity for resistance and resilience, as recent research has shown how queer people have built supportive community and drew strength from radical acceptance in the pandemic, even when institutional supports are absent (Gonzalez et al, 2021 ). Despite increasing LGBTQ + representation in government leadership positions and its correlation with growing LGBTQ + -inclusive legislation (Reynolds, 2013 ), prejudice and discrimination persist in policymaking, and the pandemic’s inordinate harms on marginalized groups like LGBTQ + people is apparent.…”
Section: Discussionmentioning
confidence: 99%